Politiser et dépolitiser la métropole : dimensions et modes de politisation de l’intercommunalité bordelaise - Gilles Pinson (Métropoles)
The article concerns politicisation of French urban inter-municipality and to question one of the topos of the literature on this subject, according to which this institutional level would be condemned to depoliticisation. In order to do this, it first reflects on the notion of politicisation, often poorly defined despite its omnipresence in the political science literature in general and the relationship between politics and administration at the local level in particular. The term politicisation actually implies processes that vary widely in their forms and purposes. To put these multiple forms of politicisation in order, three dimensions and four modes of politicisation are distinguished. The survey that inspired this typology and allowed it to be tested focused on the Bordeaux inter-municipality - - the Bordeaux urban community that became a metropolis in early 2015 - and on a period from 1995 to 2015 marked by four changes of president. This survey revealed very distinct ways for metropolitan political leaders to control recruitment and mobility within the inter-municipal administration, to embed inter-municipal debates and decisions in ideological and partisan opposition patterns and to mobilise the administration in the service of a public policy programme and more generally, a territorial project. The twenty years or so of inter-municipal history in Bordeaux shows some contrasting situations, oscillating mainly around two modes of politicisation: the politicisation of control and transformational politicisation.